2017
DOI: 10.1016/j.micpath.2017.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of flavonoids on biofilm formation by Staphylococcus aureus that overexpresses efflux protein genes

Abstract: This study evaluated the efficacy of glycone (myricitrin, hesperidin and phloridzin) and aglycone flavonoids (myricetin, hesperetin and phloretin) in inhibiting biofilm formation by Staphylococcus aureus RN4220 and S. aureus SA1199B that overexpress the msrA and norA efflux protein genes, respectively. The minimum inhibitory concentration (MIC) and minimum biofilm inhibitory concentration (MBIC - defined as the lowest concentration that resulted in ≥50% inhibition of biofilm formation) of flavonoids were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 28 publications
1
55
0
1
Order By: Relevance
“…This study suggested that phloretin also acts as an inhibitor of biofilm formation as well as an anti-inflammatory agent in inflammatory diseases [37]. Besides, Phloretin exhibited anti-biofilm formation of S. aureus RN4220 and SA1199B at low concentration with inhibitory efficiency up to 70% [38], which might function through targeting efflux proteins.…”
Section: Phloretinmentioning
confidence: 77%
“…This study suggested that phloretin also acts as an inhibitor of biofilm formation as well as an anti-inflammatory agent in inflammatory diseases [37]. Besides, Phloretin exhibited anti-biofilm formation of S. aureus RN4220 and SA1199B at low concentration with inhibitory efficiency up to 70% [38], which might function through targeting efflux proteins.…”
Section: Phloretinmentioning
confidence: 77%
“…In another study, myricetin ( 46 ) inhibited biofilm formation of S . aureus by MBIC 50 values of 1 μg/ml (Lopes, dos Santos Rodrigues, Magnani, de Souza, & de Siqueira‐Júnior, ).…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
“…All limonoids (25)(26)(27) showed a characteristic peak at m/z 189 derived from the common cleavage of ring C, followed by rearrangements, and the subsequent loss of H 2 O, which confirmed the presence of an epoxylactone system and an intact furan ring ( Figure 2, Table 2). In addition, the RDA cleavage of ring C provided a weak but diagnostically useful peak at m/z 295, suggesting a limonin skeleton ( Figure 2).…”
Section: Antibacterial Activitymentioning
confidence: 78%
“…In addition, the RDA cleavage of ring C provided a weak but diagnostically useful peak at m/z 295, suggesting a limonin skeleton ( Figure 2). The limonoids limonyl acetate (25) (27) was previously isolated from seeds of C. sinensis, 19 and it was found in all the root samples analyzed (Table 1).…”
Section: Antibacterial Activitymentioning
confidence: 99%